Uncertainty calculations in optical methods used for micro flow measurement. (December 2021) - Batista, Elsa; Furtado, Andreia; Ferreira, Maria do Céu; Godinho, Isabel; Álvares, Miguel; Afonso, Joana; Martins, Rui F.
Abstract: This work aims to describe the uncertainty calculation methodologies associated with two optical methods used for micro flow measurements, both developed at the Portuguese Institute for Quality (IPQ) under the EMPIR project MeDD II – Metrology for Drug Delivery framework. One of the methods is the front track which consists of tracking the meniscus of a liquid inside a capillary tube over time. The second method is the pending drop method that relies on measuring the volume growth of a drop over time. Both methods use a camera to capture images and convert them in volume or displacement length to determine flow rate. The uncertainty calculations will be presented in detail. The values obtained for the front track method are much smaller than for the pending drop method, specially at very low flow rates.